Outcomes of immunomodulator and advanced therapies for primary sclerosing cholangitis-associated inflammatory bowel disease. Issue 3 (17th January 2023) - Sayed, Amr; Assis, David N.; Silveira, Marina G.; Deng, Yanhong; Ciarleglio, Maria; Gaidos, Jill K.J.; Proctor, Deborah D.; Al-Bawardy, Badr
Abstract : Background: Inflammatory bowel disease (IBD) coexists in up to 80% of patients with primary sclerosing cholangitis (PSC). The aim of this study is to investigate the outcomes of immunomodulator (IMM)/advanced therapies for the treatment of PSC-IBD. Methods: This was a single-center, retrospective study of patients with PSC from 1 January 2012 to 1 April 2021. Adult patients (age ≥ 18 years) with PSC-IBD were included. Primary outcomes were rates and predictors of IMM/advanced therapies to treat PSC-IBD. Secondary outcomes included rates of cholangitis, PSC-IBD clinical remission, and endoscopic healing. Results: A total of 106 patients with PSC were reviewed and 72 (68%) with confirmed PSC-IBD were included in the study. The median age was 48 years (IQR, 33–59.5) and 69.4% were male. Overall, 28 patients (38.9%) required IMM/advanced therapies to treat PSC-IBD (22 biologic/small molecule therapy and six thiopurine monotherapy). Patients in the IMM/advanced therapies group were more likely to have small bowel involvement (32.1% vs. 4.6%; P = 0.002). In the IMM/advanced therapies group, clinical remission was achieved in 78.6% but endoscopic healing in only 50%. The rate of acute ascending cholangitis was 42.9% in the IMM/advanced therapies group compared with 31.8% in the non-IMM/advanced therapies group ( P = 0.34). Conclusion: In our cohort, up to a third of patients with PSC-IBD required IMM/advanced therapies with only 50% of these patients achieving endoscopic healing. The use of IMM/advanced therapies was not associated with a higher risk of cholangitis, but larger studies are needed to investigate the risk with different classes of advanced therapies.